Determination The Inhibitory Effect of the truffle Terfezia sp crude Extract against some types of bacterial species causes Eye infections - Nadhier Maroff, Mohammed; Laith Salih mahdi, Safa (Tikrit Journal of Pharmaceutical Sciences, 2023)
150 samples had been collected from eye patients with ages ranged between 1 month to 80 years of both genders. The patients were clients of the consultant clinic of ophthalmology Salahuddin public Hospital for the duration between October 2016 to February 2017. The results of the isolated bacteria were divided into two section: the Gram positive bacteria while represented the highest ratio in a matter of 78 isolates that represent (82%), whereas the number of the Gram negative bacteria reached 22 isolates which represents (18%). The inhibitory effect of the aqueous and spirituous extract of Terfezia sp. Was tested against the bacterial isolates that proved high resistance against antibiotics. Three different concentrations (750,1000 and1500 mg / ml) were used, and The results proved the effectiveness of the aqueous extract against most isolates with inhibitory diameter ranged between (30-9) mm, whereas the spirituous extract proved inhibitive effectiveness against three Staph. Saprophyticus isolates only with inhibition diameters of (28-8 mm)